Young and Restless, Old and Focused: Age-Differences in Mind-Wandering Frequency and Phenomenology - MORAN, CATHERINE NORA; Dockree, Paul; Mc Govern, David (My University, 2020)
The consistently observed age-accompanied diminution in mind-wandering stands seemingly opposed to accounts that present mind-wandering as a failure of executive control. This study examined the impact of aging on the frequency and phenomenology of mind-wandering and investigated distinct variables mediating age-related differences in unintentional and intentional mind-wandering. Thirty-four younger and 34 healthy older adults completed a neuropsychological test battery and contrast change detection task embedded with experience sampling probes asking participants to discriminate the nature of their thoughts.Results revealed age-related decreases in unintentional and intentional mind-wandering, but equivalent task accuracy. Parallel mediations demonstrated that older adults reduced their unintentional mind-wandering through having less anxiety and greater task engagement than younger adults. Despite evidence of age-related decline on cognitive function tests, neither executive function nor task demand variables further contributed to the model. Our results adjudicate between competing theories, highlighting the roles of affective and motivational factors in unintentional mind-wandering. Intentional mind-wandering showed no significant associations with the neuropsychological measures; however, intentional mind-wandering was associated with more false alarms, which was mediated by greater reaction time variability (RTV). In the context of the exploration/exploitation framework, we suggest that younger adults were more inclined to intentionally mind-wander, indexed by increased RTV, while preserving comparable performance accuracy to older adults. Conversely, older adults exploited greater task focus, marked by reduced RTV, with less bias toward, or resources for,exploration of the mind-wandering space.Therefore, dispositional and strategic factors should be considered in future investigations of mind-wandering across the lifespan.
ACCEPTED
Keywords: Cognitive aging; Mind-wandering; Intentionality; Negative affect; Motivation; Ageing; Neuroscience; AGE-RELATED-CHANGES; AGEING; ATTENTION; Ageing, memory and other cognitive processes; COGNITIVE AGEING; Cognitive Development/Processes; MIND-WANDERING; Third age/ageing